1992
DOI: 10.1007/bf00931651
|View full text |Cite
|
Sign up to set email alerts
|

Identification of diagnostic antigens fromTrichinella spiralis

Abstract: The Western blotting technique was used to determine the antigens of Trichinella spiralis muscle larvae that were recognized by antibodies in sera from humans and pigs displaying T. spiralis infections. This resulted in the identification of several antigens that were recognized by all sera. Some of these antigens, notably those that were recognized during the early stage of infection, cross-reacted with antibodies to other parasites. This cross-reactivity was caused by the presence of phosphorylcholine on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Most authors consider that the major antigenic fraction of Trichinella (TSL1) has a molecular mass of 45 kDa (8,10,17), and the 43-to 44-kDa doublet identified in our study could well correspond to this fraction. We chose as a specific profile the 43-to 44-kDa doublet associated with the 64-kDa band, as it was observed in 100% of the 51 patients with acute trichinellosis, in 4 out of 9 patients at the early stages of the disease, and in only 1 (1%) of 85 control subjects; this control subject had suspected anisakiasis.…”
Section: Discussionsupporting
confidence: 53%
“…Most authors consider that the major antigenic fraction of Trichinella (TSL1) has a molecular mass of 45 kDa (8,10,17), and the 43-to 44-kDa doublet identified in our study could well correspond to this fraction. We chose as a specific profile the 43-to 44-kDa doublet associated with the 64-kDa band, as it was observed in 100% of the 51 patients with acute trichinellosis, in 4 out of 9 patients at the early stages of the disease, and in only 1 (1%) of 85 control subjects; this control subject had suspected anisakiasis.…”
Section: Discussionsupporting
confidence: 53%
“…The low specificity of Trichinella CLE preparations for diagnosis of human trichinellosis has been reported previously (28,44); however, it is believed that CLE preparations may be useful for early detection of Trichinella infections (28,41,44). Although it is expected that some of the antigens contained in CLE preparations may be recognized earlier than TSL-1 antigens, the data presented here suggest that such CLE antigens either are not specific (e.g., phosphorylcholine) (18,40) or have immunogenicity below the threshold of the response induced by immunodominant cross-reactive antigens.…”
Section: Discussionmentioning
confidence: 54%
“…Over the last decades many techniques have been adapted for detecting antibodies against Trichinella antigens, such as bentonite flocculation, latex agglutination, indirect immunofluorescence (IIF), counterimmunoelectrophoresis, immunoblotting, and enzyme-linked immunosorbent assay (ELISA) (13). At present, however, ELISA techniques using either crude antigen preparations from muscle L1 larvae (10,25,28,41), whole excretory-secretory antigens (ESA) (4,9,33,42), or purified antigens (8,18,44) are the most widely used. IIF using cryosections of infected muscles or isolated larvae is also routinely used in some laboratories (17,31,37).…”
mentioning
confidence: 99%
“…The 45 kDa antigenic component was purified from freshly obtained muscle larva using two-step affinity chromatography as described by Homan et al (1992) SERUM SAMPLES Serum samples from trichinellosis patients recently received at our laboratory and from an outbreak of trichinellosis that took place in Slupsk, Poland in 1991 were used in this study. The patients here studied were all at an early stage of trichinellosis.…”
Section: Methodsmentioning
confidence: 99%
“…The 45 kDa antigenic component was purified from freshly obtained muscle larva using two-step affinity chromatography as described by Homan et al (1992) it was observed only when using sera from trichinellosis patients. In contrast, no reactivity was found using sera from echinococcosis, filariasis, cysticercosis, ascariasis, strongyloidiasis or toxocariasis patients.…”
Section: Methodsmentioning
confidence: 99%